RASIONALISASI PERSPEKTIF FILM LAYAR LEBAR BERADAPTASI KARYA SASTRA - Kartika, Pheni Cahya (Universitas Negeri Surabaya, 2016)
Film as one of super important visual media is currently growing in Indonesia. Films will only be meaningful if it meets with the audience. Indonesia's willingness to watch the movie becomes very important. According to the survey the majority of wide screen film lovers, films adapted from literary works such as novels. This research is qualitative research in the field of literary studies and concentrate on the educational value of social psychology. Based on the analysis, it can be concluded that moviegoers are more interested in the film because of adopting novel storyline that often make a good impression, especially on their personality. Literary works such as novels able to be taught and enjoyed also by the presence of the film that this requirement will be educational value. Compared with the films that did not adopt a literary work, lovers of literature are sometimes not more interested in movies with some reason considered quite rational. Differences in the way the story and imagination commercial terms was seen as reducing the spirit of a literary work's title.